(Collins primary focus) Comprehension pupil book 3 - Jackman, John (Collins Educational; London, 2011)
Collins Primary Focus: Comprehension Pupil Book 3 is aimed at ages 9+. Using a variety of well-known authors, the book is designed to encourage children to read and understand every essential fiction and non-fiction text type. Follow-up activities progress from literal questions to higher order thinking skills.Features significant authors from a range of eras including contemporary household names that children love to readIncludes every genre required by current literacy frameworksSupports all ability levels with a progression through literal, deductive, evaluative and inferential questionsEngages all children with an updated design and new artwork to complement different texts